2015
DOI: 10.1021/acs.energyfuels.5b01214
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Products from Pinewood Pyrolysis in Three Different Reactor Systems

Abstract: The product yields and selectivity from fast pyrolysis of biomass are highly dependent on the physicochemical properties of the biomass feedstock and the process conditions. The objective of this study was to compare the product yields and selectivity from fast pyrolysis of pinewood using three different reactors systems typically used in research laboratory settings for studying biomass pyrolysis: a micropyrolyzer coupled to a GC/MS system, a batch tubular reactor, and a fluidized-bed (FB) continuous reactor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
(118 reference statements)
0
15
0
Order By: Relevance
“…Levoglucosany ield can be altereda nd secondary reactions suppressed significantly by optimizing the following experimental variables:s ample size, carrier/sweep gas rate, heating rate, and biomass moisture content. [16,17,[60][61][62][63][64][65] It was demonstrated that H-ZSM-5, with aS i/Al ratio of roughly3 0, gives the best selectivity to aromaticsc omparedt oa morphous silica-aluminas, other zeolites,a nd other supported metal or metal oxide catalysts. Thus, slow heating rates maximize the amount of useable levoglucosan.…”
Section: Pyrolysis Of Cellulose and Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…Levoglucosany ield can be altereda nd secondary reactions suppressed significantly by optimizing the following experimental variables:s ample size, carrier/sweep gas rate, heating rate, and biomass moisture content. [16,17,[60][61][62][63][64][65] It was demonstrated that H-ZSM-5, with aS i/Al ratio of roughly3 0, gives the best selectivity to aromaticsc omparedt oa morphous silica-aluminas, other zeolites,a nd other supported metal or metal oxide catalysts. Thus, slow heating rates maximize the amount of useable levoglucosan.…”
Section: Pyrolysis Of Cellulose and Glucosementioning
confidence: 99%
“…Selectivity to aromatic products or value-added chemicals was determined to be af unction of catalyst/biomass weightr atio, heating rate, pore size, reactorc onfiguration, and reactiontemperature. [16,17,[60][61][62][63][64][65] It was demonstrated that H-ZSM-5, with aS i/Al ratio of roughly3 0, gives the best selectivity to aromaticsc omparedt oa morphous silica-aluminas, other zeolites,a nd other supported metal or metal oxide catalysts. [60,63,[66][67][68][69][70][71] However, physical mixtures of Siral 5, an amorphous silica-alumina, and H-ZSM-5 was shown to have as ynergistic effect on the yield of aromaticsr elative to either catalystalone.…”
Section: Pyrolysis Of Cellulose and Glucosementioning
confidence: 99%
“…It has been found that the overall yield and product distribution among broad chemical classes were similar for Pinus radiata and grape marc pyrolysed in a Py-GC/MS system (Subagyono et al, 2016b) and in a short residence time flow reactor (Subagyono et al, 2015a). Likewise, product distribution for pinewood pyrolysis in a Py-GC/MS system was generally similar to that for the same wood pyrolysed in a short residence time fluidized bed reactor (Zmiewski et al, 2015). Finally, the conversions in several different classes of fast pyrolysis reactors have been found to be similar (Bridgwater, 2012).…”
Section: Introductionmentioning
confidence: 81%
“…In addition to the feedstock properties there are various factors in how the pyrolysis process is conducted and this includes, type and material of the reactor [92] as well as the use of catalysts [93]. The use of potential catalysts will be discussed later in chapter 4.2.2, but due to saving costs and fulfil the aims of the research mentioned earlier in chapter 1.1, the actual use of catalysts for this project is not investigated.…”
Section: Factors Affecting the Pyrolysis Outputmentioning
confidence: 99%
“…The specific factors effecting oil output will be discussed in the next paragraph. Furthermore, the operation itself such as the maximum temperature and heating ramp [92], are one of the obvious factors which can be controlled in order to influence the quality of the output.…”
Section: Factors Affecting the Pyrolysis Outputmentioning
confidence: 99%